Construção dos objetos de discurso em artigos mediáticos de divulgação científica para crianças - Ramos, Rui (2014)
This study examines the relevant aspects of textual construction of science communication media articles explicitly aimed at children and youth. It assumes that the relationship established by the enunciator with the entities which are present in their discourse can be recognized from their objects of discourse. These reveal the points of view or, in other terms, the modality operated by discourse and embodied in the texts. The study also adopts the concept of “communication contract” (Charaudeau, 2006), which takes in consideration the set of conventions that shape the verbal exchange. In particular, it focuses on the identity of potential readers, with its own encyclopaedia, strongly conditioning the adoption of textual models, the choice of objects of discourse and the pragmatic objectives – in particular, to “inform and attract” (Giering & Souza, 2013). The corpus consists of public communication of science articles published in the magazines Mega Power and Visão Júnior, two monthly publications aimed at children and youth, in September 2013.